2021
DOI: 10.1016/j.jtho.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase 2 Studies of Checkpoint Inhibitors Alone or in Combination With Pegilodecakin in Patients With Metastatic NSCLC (CYPRESS 1 and CYPRESS 2)

Abstract: Jotte has received honoraria, served on a speakers' bureau, and received travel accommodations from Bristol-Myers Squibb and Roche/Genentech. Dr. Nemunaitis is an employee of Gradalis with stock and ownership interests and patents, royalties, and other intellectual properties; has received honoraria from AstraZeneca, served as a consultant with Symvivo, served on the speakers' bureau for AstraZeneca; and provided expert testimony for Foundation Medicine. Dr. Schneider has received honoraria from Foundation Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…For example, IL-10 agonism and antagonism have been observed to enhance anti-tumor outcomes, preclinically [114,115]. Despite promising early phase results, IL-10 agonist, pegilodecakin, failed to enhance response to FOLFOX in the 2nd line for mPDAC [116] and led to increased toxicity without enhancing survival when paired with aPD-1 therapy in NSCLC [117]. Human trials with IL-10 inhibition are limited.…”
Section: Il-10 Modulationmentioning
confidence: 99%
“…For example, IL-10 agonism and antagonism have been observed to enhance anti-tumor outcomes, preclinically [114,115]. Despite promising early phase results, IL-10 agonist, pegilodecakin, failed to enhance response to FOLFOX in the 2nd line for mPDAC [116] and led to increased toxicity without enhancing survival when paired with aPD-1 therapy in NSCLC [117]. Human trials with IL-10 inhibition are limited.…”
Section: Il-10 Modulationmentioning
confidence: 99%
“…In relapsed pancreatic cancer, a phase III clinical trial showed no statistical difference between FOLFOX (folinic acid + fluorouracil + oxaliplatin) in association with pegylated IL-10 compared to FOLFOX alone [62]. Unfortunately, in metastatic NSCLC patients, the addition of IL-10 to PD-L1 inhibitors, either nivolumab or pembrolizumab, did not bring any benefit [63].…”
Section: Il-10 As An Anti-tumor Cytokinementioning
confidence: 99%
“…13,14,16 Pegilodecakin exhibited single-agent activity in renal cell carcinoma and melanoma, and correlative studies support evidence of pharmacodynamic activity at the recommended phase 2 dose and schedule. 11,16,17 Evidence of immune activation and reduction of immunosuppressive TGF-b levels were seen with pegilodecakin in CYPRESS-1 and -2, but these did not translate into better clinical outcomes. Did the changes in peripheral blood reflect changes in the tumor?…”
mentioning
confidence: 99%
“…In this issue of the Journal, Spigel et al 11 present the results of two randomized signal-finding trials in checkpoint inhibitor-naive patients, adding pegilodecakin to PD-1 inhibitor monotherapy. Pegilodecakin is a recombinant pegylated formulation of interleukin (IL)-10 that allows longer half-life and greater antitumor activity in preclinical and clinical studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation